2004
DOI: 10.1111/j.1600-6143.2004.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of CXCR3-Binding Chemokines in Urine Indicates Acute Renal-Allograft Dysfunction

Abstract: A noninvasive urinary test that diagnoses acute renal allograft dysfunction would benefit renal transplant patients. We aimed to develop a rapid urinary diagnostic test by detecting chemokines. Seventythree patients with renal allograft dysfunction prompting biopsy and 26 patients with stable graft function were recruited. Urinary levels of CXCR3-binding chemokines, monokine induced by IFN-c (Mig/CXCL9), IFN-c -induced protein of 10 kDa (IP-10/CXCL10), and IFN-inducible T-cell chemoattractant (I-TAC/CXCL11), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
122
1
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 21 publications
10
122
1
6
Order By: Relevance
“…Urinary measurements of MIG in a small number of pediatric patients (33) and in adult renal allograft patients support our data (34,35). Nevertheless, so far no study has shown the day-to-day value of urinary CXCR3 ligand measurements in a nonselected group of de novo NTX patients and the predictive value of MIG in urine for the diagnosis of AR.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Urinary measurements of MIG in a small number of pediatric patients (33) and in adult renal allograft patients support our data (34,35). Nevertheless, so far no study has shown the day-to-day value of urinary CXCR3 ligand measurements in a nonselected group of de novo NTX patients and the predictive value of MIG in urine for the diagnosis of AR.…”
Section: Discussionsupporting
confidence: 61%
“…Similar to MIG, but to a lesser extent, high urinary IP-10 correlated well with AR as shown previously (34). It is intriguing, however, that the upregulation of IP-10 gene activity might not be that strictly dependent on IFN and has also been associated with alloantigen-independent organ damage (37,38).…”
Section: Discussionmentioning
confidence: 48%
“…38,39 Studies in diverse tissues including the brain, liver, and lung suggest that CXCR3 does not provide a tissue-specific signal for lymphocyte recruitment but is associated with infiltration of inflamed tissues regardless of the anatomical site. 36,40,41 Although these studies have shown expression of CXCR3 ligands associated with CXCR3 ϩ lymphocytes in inflammatory disease, functional studies have been limited to demonstrating that lymphocytes isolated from diseased tissues undergo chemotaxis to CXCR3 ligands. 21 In the present study we found increased expression of all three CXCR3 ligands in several different chronic inflammatory liver diseases whereas the levels in normal liver were minimal.…”
Section: Discussionmentioning
confidence: 99%
“…36 A elevação urinária do TGF-b tem sido associada também ao grau de fibrose intersticial na IF/TA. 52,53 Hu et al, 54 analisando amostras únicas de urina pré-biópsia renal de 99 pacientes, demonstraram elevação de I-TAC/CXCL11, MIG/CXCL9 e IP-10/ CXCL10 em vigência de RA, nefropatia por poliomavírus e NTA, mas não em casos de rejeição borderline, IF/TA e função estável de enxerto. MIG/CXCL9 e IP-10/CXCL10 apresentaram ní-veis mais elevados, com sensibilidade de 88,6% e especificidade de 87% para diagnóstico das complicações mencionadas.…”
Section: Citocinas E Quimiocinas No Tecido Renal E No Sangue De Transunclassified
“…MIG/CXCL9 e IP-10/CXCL10 apresentaram ní-veis mais elevados, com sensibilidade de 88,6% e especificidade de 87% para diagnóstico das complicações mencionadas. 54 Ressalta-se ainda que, com o tratamento da RA, os níveis urinários de MIG/CXCL9 e IP-10/CXCL10 se reduziram dias antes da diminuição da creatinina sanguínea. IP-10/CXCL10 urinária se reduziu em todos os pacientes 2 a 5 dias antes da diminuição da creatinina sérica.…”
Section: Citocinas E Quimiocinas No Tecido Renal E No Sangue De Transunclassified